The Analysis of Metacognitive Ability of Boarding School Students Towards the Subject on Ecosystem - Febri Maswandi (Universitas Sebelas Maret, 2015)
This research aims to determine the level of metacognitive abilities in boarding school students towards biology learning on the subject of the ecosystem and relationship knowledge of cognition and regulation of cognition. The subjects of this researchare the students of class X in one of the boarding schools in Sukabumi. The Metacognitive Awareness Inventorythat is modified from Schraw and Dennison (1994) is used in this research in orderto reveal the metacognitive skills. The result shows thatmost students have sufficient metacognitive skills. Besides, the students have also a sufficient level of capability in the aspects of cognition and regulation of cognition. Knowledge of cognition has a significant relation towards regulation of cognition.Keywords: Metacognitive, metacognitive knowladge, regulation of cognition